Protein phosphorylation profiling identifies potential mechanisms for direct immunotoxicity. (2nd January 2016) - Shao, Jia; Stout, Inge; Hendriksen, Peter J. M.; van Loveren, Henk; Peijnenburg, Ad A. C. M.; Volger, Oscar L.
Abstract: Signaling networks are essential elements that are involved in diverse cellular processes. One group of fundamental components in various signaling pathways concerns protein tyrosine kinases (PTK). Various toxicants have been demonstrated to exert their toxicity via modulation of tyrosine kinase activity. The present study aimed to identify common cellular signaling pathways that are involved in chemical-induced direct immunotoxicity. To this end, an antibody array-based profiling approach was applied to assess effects of five immunotoxicants, two immunosuppressive drugs and two non-immunotoxic control chemicals on the phosphorylation of 28 receptor tyrosine kinases and 11 crucial signaling nodes in Jurkat T-cells. The phosphorylation of ribosomal protein S6 (RPS6) and of kinases Akt, Src and p44/42 were found to be commonly regulated by immunotoxicants and/or immunosuppressive drugs (at least three compounds), with the largest effect observed upon RPS6. Flow cytometry and Western blotting were used to further examine the effect of the model immunotoxicant TBTO on the components of the mTOR-p70S6K-RPS6 pathway. These analyses revealed that both TBTO and the mTOR inhibitor rapamycin inactivate RPS6, but via different mechanisms. Finally, a comparison of the protein phosphorylation data to previously obtained transcriptome data of TBTO-treated Jurkat cells resulted in a good correlation at the pathway level and indicated that TBTO affects ribosome biogenesis and leukocyte migration. The effect of TBTO on the latter process was confirmed using a CXCL12 chemotaxis assay.